Pengaruh Gaya Mengajar Guru terhadap Peningkatan Prestasi Belajar SMPIT Al Mawaddah Warrahmah Kolaka - Afra Nurul Aqiilah; Sulkifli Ar (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of teachers’ teaching style on students’ learning achievement at SMP IT Al-Mawaddah Warrahmah Kolaka. Teaching style is considered an important factor in creating an effective learning environment that can encourage students’ academic success. The research employed a quantitative approach using a simple linear regression analysis to examine the relationship between the independent variable, namely teachers’ teaching style, and the dependent variable, students’ learning achievement. Data were collected through questionnaires and documentation of students’ academic scores, which were then analyzed statistically to test the proposed hypothesis. The results of the analysis indicate that the correlation coefficient value (R) is 0.931, while the coefficient of determination (R²) is 0.867. These findings suggest that teachers’ teaching style contributes significantly to students’ learning achievement. Furthermore, the significance value obtained was 0.001, which is smaller than 0.05, indicating a positive and statistically significant effect. Therefore, it can be concluded that the better and more appropriate the teaching style applied by teachers, the higher the students’ academic achievement. This study highlights the importance of improving teaching strategies to support optimal learning outcomes.